IN VITRO ANTIOXIDANT, ANTIMICROBIAL AND ADMET STUDY OF NOVEL FURAN/BENZOFURAN C-2 COUPLED QUINOLINE HYBRIDS - Rajpurohit, Anantacharya; Satyanarayan, Nayak D.; Patil, Sameer; Mahadevan, Kittappa M.; J., Adarsha H. (International Journal of Pharmacy and Pharmaceutical Sciences, 2017)
Objectives: Synthesis of novel 2-(benzofuran-2-yl) and 2-(furan-2-yl) quinoline-4- carboxylates and their [2-(1-benzofuran-2-yl) quinolin-4-yl] methanol, [2-(1-furan-2-yl) quinolin-4-yl] methanol and its derivatives for antioxidant, antimicrobial and ADMET study. Methods: Synthesis was carried with conventional method and the structures were confirmed by IR, 1H NMR, 13C NMR and mass spectral analysis. The antioxidant activity was performed by DPPH and H2O2 radical scavenging method. Antimicrobial investigation was established by cup plate and food poison technique. The in silico absorption, distribution, metabolism, excretion and toxicity (ADMET) study of the drug was carried out in ACD/lab-2. Results: The antioxidant activity results revealed that, compounds 4b-c, 5a-b, 10c and 10f exhibited good DPPH radical and hydrogen peroxide scavenging activity. The antibacterial results revealed that, compounds 4c, 5a-b, 10b, 10d and 10f exhibited good activity against Escherichia coli, Klebsiella pneumonia and Salmonella typhimurium. Further, the antifungal activity results showed that, compounds 4c, 5c and 10c-e were showing good activity against Aspergillus flavus and Candida neoformans. Â The mean value of P<0.05 were considered to be statistically significant. The ADMET results revealed that compounds emerged as a potential candidate for antioxidant and antimicrobial agents. Conclusion: The study reveals that compounds containing furan/benzofuran coupled heterocycles are play the important role for activity as they possess potent antioxidant and antimicrobial agents. The in silico ADME analysis also suggesting the compounds were in acceptable range to obey the pharmacokinetic parameters.Â 